Determination of Saponins in Leaves of Four Swiss Chard ( Beta vulgaris L.) Cultivars by UHPLC-CAD/QTOF-MS/MS - Agnieszka Mroczek; Urszula Klimczak; Mariusz Kowalczyk (Polish Journal of Food and Nutrition Sciences)
Swiss chard is a vegetable valued not only for the taste of its leaves but also because of its health-promoting properties. To date, nothing is known regarding the occurrence of saponins in the Swiss chard plant, even though they could be at least partially responsible for the nutraceutical activities of this plant. This research aimed to describe saponins from the leaves of four Swiss chard ( Beta vulgaris L.) cultivars. Saponin structures were analyzed by UHPLC-CAD/QTOF-MS/MS. Based on the fragmentation patterns, we tentatively identified 16 triterpene saponins in B. vulgaris , including two that had not been detected previously. The observed compounds were glycosides of five different, tentatively identified aglycones, i.e ., oleanolic acid, hederagenin, gypsogenin, akebonoic acid, and serjanic acid. Moreover, the structure of four saponins detected in Swiss chard leaves included dioxolane-type and six acetal-type substituents. Eleven, eight, eleven, and eight saponins were observed in saponin fractions obtained from Rhubarb, Bulls Blood, Perpetual Spinach, and White Silver cultivars, respectively. Furthermore, the content of all identified triterpene derivatives in the investigated cultivars was estimated using a method based on the UHPLC coupled with QTOF-MS/MS and charged aerosol detector (CAD). The analyzed cultivars differed in the total and individual saponin content. The total saponin content ranged from 125.53 to 397.09 μg/g DW.